Организационно-управленческий подход к системе труда: «школа человеческих отношений и «теория человеческого капитала» (Путеводитель предпринимателя)
The article is devoted to the problems of organizational-administrative approach to the labor systems. The organization is considered as a complicated system consisting of people (employees, personnel). Methods, useful for conditions of formation and development of market relations, to manage social-labor relationship are specified.